Penerapan Metode Extreme Learning Machine untuk Peramalan Harga Cryptocurrency - Leonardo Tejaya; Desi Arisandi; Janson Hendryli (STMIK Banjarbaru, 2023)
Cryptocurrency is in great demand as an investment medium to gain financial benefits. A common problem that is often faced is how to predict the movement of the value of electronic money in the future. Investors/traders usually only see price movements and buy/sell Cryptocurrency assets intuitively, so mistakes often occur in making transactions. To anticipate and minimize this, you can use an algorithm that can help predict Cryptocurrency price movements. Extreme Learning Machine (ELM) is a development method of a simple feedforward neural network using one hidden layer or commonly known as Single Hidden Layer Feedforward Neural NetworksTesting is done by doing several trials for each percentage value, namely 60%, 65%, 70%, 75%, 80%. Tests were carried out using the binary sigmoid activation function, the number of hidden neurons was 20 and the weight range was [-1,1]. The best prediction results using MAPE are generated on Bitcoin data with the smallest error value of 2.8590%Keywords: Cryptocurrency; Investation; Extreme Learning Machine; Prediction AbstrakCryptocurrency banyak diminati untuk menjadi media investasi dalam meraih keuntungan finansial. Masalah umum yang sering dihadapi adalah bagaimana meramalkan pergerakan nilai dari uang elektronik pada masa mendatan. Investor/trader biasanya hanya melihat pergerakan harga dan melakukan jual/beli aset Cryptocurrency secara intuitif, sehingga sering terjadi salah dalam melakukan transaksi. Untuk mengantisipasi dan meminimalisir hal tersebut maka dapat menggunakan sebuah algoritme yang dapat membantu dalam meramalkan pergerakan harga Cryptocurrency. Extreme Learning Machine (ELM) merupakan metode pengembangan dari jaringan syaraf tiruan feedforward sederhana dengan menggunakan satu hidden layer atau biasa dikenal dengan Single Hidden Layer Feedforward Neural Networks. Pengujian dilakukan dengan melakukan beberapa kali percobaan untuk setiap nilai persentase yaitu 60%, 65%, 70%, 75%, 80%. Pengujian dilakukan menggunakan fungsi aktivasi sigmoid biner, jumlah hidden neuron 20 serta rentang bobot [-1,1]. Hasil prediksi terbaik menggunakan MAPE dihasilkan pada data Bitcoin dengan nilai kesalahan terkecil yaitu 2.8590%Kata Kunci: Cryptocurrency; Investasi; Extreme Learning Machine; Prediksi